Eutrophication, Nile perch and food-web interactions in south-east Lake Victoria - Cornelissen, I. J. M. (Wageningen University, 2015)
The present study investigates the bottom-up effects of eutrophication on the Nile perch and food-web dynamics in south-east Lake Victoria. We analysed the level of eutrophication along an eutrophication gradient in the Mwanza Gulf. Phytoplankton biomass varied spatially and seasonally and was limited by nutrients in deep water and by light in shallow water. Fish distributions were dynamic, with environmental factors depth and temperature influencing Nile perch size structure and distribution patterns similarly on small and large spatial scales.